COVID-19 anthropause affects coral reef ecosystems through biophysical changes - Elizabeth M. P. Madin; Aviv Suan; Sarah J. L. Severino; Anita O. Tsang; Joshua S. Madin; Zackery Rago; Ian Gerber; Ku‘ulei S. Rodgers (npj Ocean Sustainability)
Abstract The COVID-19 pandemic induced a global ‘anthropause’. By changing human patterns of movement, the microscopic pathogen behind the pandemic indirectly caused dramatic effects on wildlife. We quantified environmental and biological responses to the COVID-19-induced complete loss—and eventual return—of human visitors to Hanauma Bay in Hawai‘i, USA. We show that the pathogen SARS-CoV-2 altered human behavior and indirectly increased water clarity, altered endangered Hawaiian monk seal behavior, and changed reef fish densities and behavior, including the key functional role of herbivore grazing. Our findings demonstrate that reduced human visitation allowed multiple biophysical ecosystem parameters to shift towards presumably ‘natural’ levels, and by extension, that human presence has an inhibitory effect on reef ecosystems. Given reef tourism’s importance to local economies and the cultural, spiritual, and economic value of reefs to Indigenous and other communities, managers must find an acceptable balance between tourism and ecological preservation of coral reefs.